Islam Nusantara Sebagai Identitas Keberagamaan di Indonesia: Telaah Terhadap Nilai Pokok Ajaran Perspektif Hadist - Budi Ichwayudi; Syabrowi Syabrowi (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2023)
This article discusses the relevance of Islam Nusantara with hadith. As is well known, Islam Nusantara has long been discussed by both academics and the general public. Its presence reaps the pros and cons. Some consider it different from the basic values ​​of Islamic teachings. There are also those who say that Islam Nusantara has a connection with socio-cultural processes, the acculturation of the entry of Islam and archipelago culture. This article was written to analyze the values ​​that exist in the concept of Islam Nusantara according to the perspective of the Prophet's hadith. The method used is a qualitative method by utilizing documentation instruments in the form of books, scientific papers, and so on. The data is taken from written literature on Islam Nusantara and is also relevant. Before being linked to the hadith, an explanation of Islam Nusantara was first put forward in the view of leading Islamic figures in Indonesia. This research gives the result that Nusantara Islam has values ​​that are relevant to the traditions of the Prophet such as tolerance, ukhuwwah Islamiyyah, mutual strengthening, and mutual love for one another. These values ​​have been mentioned in the main books of hadith such as the books of Ṣaḥiḥ Bukhārī, Musnad Aḥmad and Sunan Abū Dāwud.